The Influence of Modern Transformation Leadership from The Director of The Travel Bureau, Work Motivation, Work Discipline on Employee Performance at PT. Kusuma Citra Travelindo Surabaya - Indrasto Kurniadi (Economic and Bussiness Faculty, Dr Soetomo University, 2023)
The aim of this study was to examine the combined and individual effects of the Main Director's leadership, work motivation, and work discipline on employee performance at PT. Kusuma Citra Travelindo Surabaya. The study included the entire population of PT. Kusuma Citra Travelindo Surabaya, which consisted of 30 individuals including the Main Director and non-permanent employees. Due to the small population size, a census technique was employed as the sampling method. The findings revealed that leadership, work motivation, and work discipline had a positive influence on the performance of Travel Bureau employees. The correlation coefficient analysis indicated a significant and moderately strong relationship between the Main Director's leadership variables, work motivation, work discipline, and employee performance. Specifically, work discipline emerged as the variable with the most dominant effect on employee performance, as evidenced by its greater standardized beta coefficient value compared to the other variables. To summarize, this study highlights that the leadership of the Main Director, along with work motivation and work discipline, significantly contribute to employee performance in the Travel Bureau. Among these variables, work discipline appears to have the greatest impact on employee performance. The findings imply the importance of fostering work discipline in enhancing employee performance, offering valuable insights for the management and HR practices of PT. Kusuma Citra Travelindo Surabaya.